Overmacht And Unforeseen Circumstances In Agreements According To Indonesian Civil Law And Dutch Law - Fitri Fatmawati, Vera; Sulistiyono, Adi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
An agreement generally includes a clause on force majeure. This is so that the parties understand between negligence caused by the parties themselves and negligence that occurs due to force majeure. This research is a normative-research that studies legal objectives, values of justice, validity of legal rules, legal concepts, and legal norms. The source materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Primary legal materials are the Indonesian Criminal Code and the Dutch Criminal Code. Furthermore, the data collected is analyzed qualitatively. Overmacht is intended to provide protection to one of the parties harmed in an agreement, provided that the objective and/or subjective conditions of a situation can be classified as overmacht. Overmacht is a common clause in an agreement in Indonesia, the regulation of this clause is found in the Civil Code in Article 1244 and Article 1245, the position of Overmacht in an agreement is in the main agreement, not separate as an additional agreement and associated with the main agreement. Dutch contract law places great importance on the agreement reached between the parties to the contract. Therefore, Dutch courts are reluctant to set aside binding agreements on grounds based on force majeure events and unforeseen circumstances. Contracting parties should scrutinize carefully the agreed risk allocation (e.g. when drafting a force majeure clause) between them before signing the agreement, as ultimately, the agreed risk allocation set out in the agreement, will most likely be upheld.